PAID UP INSURANCE DAN EXTENDED INSURANCE PADA ASURANSI JIWA BERJANGKA UNTUK STATUS HIDUP GABUNGAN - Risma Rio Pratiwi; Rolan Pane; Musraini ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Insurance companies provide the extended insurance policy and paid up insurance to policyholders  who canceled the insurance contract.  This policy aims to prevent the insurance company and the  policyholders  from losing their money.  This article discusses the extended insurance and insurance paid up of a joint life  policyholders whose age are  x  and  y  years joining  a term life insurance program.  The evaluation of  extended insurance and paid up insurance uses the commutation symbol. A  numerical example is given at the end of the discussion to show the implementation of the case discussed.PAID UP INSURANCE DAN EXTENDED INSURANCE PADA ASURANSI JIWA BERJANGKA UNTUK STATUS HIDUP GABUNGAN